Student Perceptions of ICT-Based Lecture Delivery During COVID-19 Pandemic - Baba, U. A.; Ishaq, M. I.; Mohammed, A.; Halliru, I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
The COVID-19 pandemic forced schools to adopt online learning methods. This study investigates the impact of Information and Communication Technology (ICT) usage on student performance in Adamawa State, Nigeria, focusing on Yola North Local Government. A quantitative approach employed a survey questionnaire distributed to 170 participants (students, teachers, and principals). Descriptive statistics analysed demographic profiles, ICT access, online learning satisfaction, and perceived barriers. While many students and teachers agreed they had sufficient IT skills, access to equipment and internet connectivity was limited. Zoom was the preferred online learning tool, but challenges like inconsistent communication, difficulty participating, and limited practical sessions were reported. Barriers included lack of consistent power supply, poor learning environment, and limited access to materials. ICT played a crucial role in continuing education during the pandemic, but significant challenges remain. Improved access to resources, better connectivity, and enhanced online learning practices are essential for optimizing student performance in future disruptions.